Maternal nutrient restriction in early pregnancy increases the risk of late embryo loss despite no effects on peri-implantation interferon-stimulated genes in suckler beef cattle. (February 2020) - Serrano-Pérez, B.; Molina, E.; Noya, A.; López-Helguera, I.; Casasús, I.; Sanz, A.; Villalba, D.
Abstract: Reducing feeding costs in suckler beef herds to improve economic returns could have detrimental impacts on fertility. This study sought to determine whether maternal nutrient restriction during early pregnancy affects interferon-stimulated gene (ISG) expression in peripheral blood mononuclear cells during the peri-implantation period in two beef cattle breeds. Relationships were also examined between subnutrition and pregnancy failure defined according to ISG fold changes on Days 18 and 21 and to plasma pregnancy specific protein B (PSPB) concentrations on Day 28 post-artificial insemination (AI). Pirenaica or Parda de Montaña dams were assigned to a control ( n = 23) or subnutrition ( n = 30) group, receiving 100% or 65% of their estimated nutritional requirements from Day 1 to 82 post-AI, respectively. Treatment did not affect ISG expression or fertility. According to ISG fold changes (chi-square P = .023) or PSPB levels (chi-square P = .04) recorded in the subnutrition group, late embryo loss was more likely than in controls. Positive correlation was detected between Day 28 PSPB concentrations and both Day 18 MX1, MX2 and ISG15 expression, and Day 21 OAS1 expression. OAS1 and MX1 fold changes were found to be the best variables to discriminate pregnancy status. Our findings indicate that maternal nutrient restriction during the first third of pregnancy does not impair embryo signalling yet may increase the risk of pregnancy failure. Highlights: Maternal subnutrition in suckler beef cattle does not impair conceptus signalling. Nutrient restriction in early pregnancy may increase the risk of pregnancy failure. OAS1 and MX1 fold changes were the best variables to predict pregnancy status.